2015
DOI: 10.1111/liv.12992
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin is an independent prognostic factor for transplant‐free survival in cirrhosis

Abstract: Serum copeptin concentration increases significantly along with the severity of cirrhosis as defined by the Child-Pugh classification. A high serum copeptin concentration predicts survival, particularly at 6 months, independently of liver-specific scoring systems in a heterogeneous population of hospitalized cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
(49 reference statements)
3
18
0
Order By: Relevance
“…The most relevant point to come out of this study by Solà et al is the internal (using the bootstrapping technique) and external validation (using 120 patients from the CANONIC study [2] with the same eligibility criteria as the study cohort) of the prognostic value of copeptin, independently of the MELD score and leukocyte count. We observed a similar prognostic value of copeptin in 184 cirrhotic patients, entering age, C-reactive protein (CRP) and MELD as covariables together with copeptin [3], instead of leukocyte count and MELD, as done in the Spanish study [1].…”
Section: To the Editormentioning
confidence: 59%
See 2 more Smart Citations
“…The most relevant point to come out of this study by Solà et al is the internal (using the bootstrapping technique) and external validation (using 120 patients from the CANONIC study [2] with the same eligibility criteria as the study cohort) of the prognostic value of copeptin, independently of the MELD score and leukocyte count. We observed a similar prognostic value of copeptin in 184 cirrhotic patients, entering age, C-reactive protein (CRP) and MELD as covariables together with copeptin [3], instead of leukocyte count and MELD, as done in the Spanish study [1].…”
Section: To the Editormentioning
confidence: 59%
“…Before recommending the use of copeptin measurement, together with the MELD score to better categorize the severity of cirrhotic patients, we wish to add some comments. Although the Spanish study enrolled a higher number of patients than our recent study on this topic (n = 184) [3], the sample size (n = 120) of the cohort used for the external validation is quite small and the prognostic value of copeptin deserves to be further validated externally. We suspect that the number of events (death and liver transplantation are not indicated) among the 120 randomly selected patients was low, since only two variables (copeptin and MELD) were entered into the prognostic model.…”
Section: To the Editormentioning
confidence: 96%
See 1 more Smart Citation
“…The pathophysiological importance of galectin 3 in cirrhosis is yet unknown. Kerbert et al [74] confirmed increased copeptin in cirrhosis and reported relations to circulatory dysfunction, severity of cirrhosis and to transplant-free survival. Experimental and clinical results from the same group showed that copeptin correlated with MELD and MELD-Na scores indicating a potential benefit of combining copeptin with specific prognostic scores [75].…”
Section: New Vasoactive Peptides In Cirrhosis: Organ Extraction and Rmentioning
confidence: 93%
“…cardiovascular instability, chronic heart failure, sepsis) disturbances of the vasopressinergic system contribute to disease pathogenesis 3 . Current reports have demonstrated that a high serum copeptin concentration predicts survival in a heterogeneous population of hospitalized liver cirrhosis (LC) patients, independent of liver-speci c scoring systems 4 , suggesting that copeptin has the potential to be a biomarker of disease progression and prognosis in LC 5 .…”
Section: Introductionmentioning
confidence: 99%